2000
DOI: 10.1161/01.res.86.11.1153
|View full text |Cite
|
Sign up to set email alerts
|

ADP-Ribosyl Cyclase in Rat Vascular Smooth Muscle Cells

Abstract: Abstract-We investigated whether ADP-ribosyl cyclase (ADPR-cyclase) in rat vascular smooth muscle cells (VSMCs) has enzymatic properties that differ from the well-characterized CD38-antigen ADPR-cyclase, expressed in HL-60 cells. ADPR-cyclase from VSMCs, but not CD38 ADPR-cyclase from HL-60 cells, was inhibited by gangliosides (10 mol/L) GT 1B , GD 1 , and GM 3 . Preincubation of membranes from CD38 HL-60 cells, but not from VSMCs, with anti-CD38 antibodies increased ADPR-cyclase activity; CD38 antigen was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…Activation of the cADPR pathway by ACh in duodenum myocytes is shown by: (1) inhibition of Ca 2+ oscillations by application of the cADPR competitive antagonist (8Br-cADPR), (2) inhibition of ACh-induced Ca 2+ oscillations by inhibitors of ADP-ribosyl cyclase (ZnCl 2 , anti-CD38 antibody) and (3) detection of ADP-ribosyl cyclase activity by fluorescence experiments as the enzyme cyclizes NGD+ (non fluorescent) to produce cGDPR, a fluorescent compound (Graeff et al, 1994). This method has been used successfully in microsomes and cellular homogenates from bovine chromaffin cells (Morita et al, 1997), rat vascular myocytes (de Toledo et al, 2000) and human myometrium (Chini et al, 2002). We were able to detect ADP-ribosyl cyclase activity in single permeabilized cells under the same conditions that we used for Ca 2+ measurements.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Activation of the cADPR pathway by ACh in duodenum myocytes is shown by: (1) inhibition of Ca 2+ oscillations by application of the cADPR competitive antagonist (8Br-cADPR), (2) inhibition of ACh-induced Ca 2+ oscillations by inhibitors of ADP-ribosyl cyclase (ZnCl 2 , anti-CD38 antibody) and (3) detection of ADP-ribosyl cyclase activity by fluorescence experiments as the enzyme cyclizes NGD+ (non fluorescent) to produce cGDPR, a fluorescent compound (Graeff et al, 1994). This method has been used successfully in microsomes and cellular homogenates from bovine chromaffin cells (Morita et al, 1997), rat vascular myocytes (de Toledo et al, 2000) and human myometrium (Chini et al, 2002). We were able to detect ADP-ribosyl cyclase activity in single permeabilized cells under the same conditions that we used for Ca 2+ measurements.…”
Section: Discussionmentioning
confidence: 91%
“…To confirm the involvement of cADPR, ADP-ribosyl cyclase activity was inhibited in permeabilized cells using ZnCl 2 (de Toledo et al, 2000), high concentrations of NGD+ and an anti-CD38 antibody (Sternfeld et al, 2003). Application of 2 mM ZnCl 2 decreased significantly the amplitude of ACh-induced Ca 2+ responses and suppressed Ca 2+ oscillations (Fig.…”
Section: Involvement Of Cadpr In Ach-induced Ca 2+ Oscillationsmentioning
confidence: 90%
“…The components of this pathway are present and functional in myometrial, vascular and airway smooth muscle cells (18)(19)(20)(21)(22)(23)(24). One important observation is the fact that the intracellular Ca 2+ transients induced by oxytocin are dependent on both the CD38/cADPR signaling pathway and extracellular Ca 2+ in human myometrial cells.…”
Section: Role Of Cadpr In Agonist-stimulated Ca 2+ Transientsmentioning
confidence: 99%
“…We have shown that cADPR is important for agonist-stimulated Ca 2+ transients in smooth muscle cells (18)(19)(20)(21). Since RyR activity appears to be important for the gating of the store-operated Ca 2+ entry channels and A, Cell extracts were prepared in RIPA buffer, proteins adjusted to 200 µg/vial and 2 µg rabbit polyclonal anti-TRPC antibodies added overnight.…”
Section: Role Of the Ryr In The Store-operated Ca 2+ Transient Pathwamentioning
confidence: 99%
“…Mounting evidence has indicated that ADPR-cyclase(s) other than CD38 may exist in the kidney, brain, and the heart (40,45), including various cells (30,(45)(46)(47). The first clues to the existence of novel ADPR-cyclase(s) emerged from experiments of the comparison of tissue cADPR levels in CD38 wild type and knockout mice (40).…”
Section: Diabetic Nephropathy and The Renin-angiotensin-aldosterone Smentioning
confidence: 99%